Group A streptococcal bacteremias in Southwest Finland 2007–2018: epidemiology and role of infectious diseases consultation in antibiotic treatment selection - Vilhonen Johanna; Vuopio Jaana; Vahlberg Tero; Gröndahl-Yli-Hannuksela Kirsi; Rantakokko-Jalava Kaisu; Oksi Jarmo (SPRINGER, 2022)
The incidence of invasive group A streptococcal (GAS) infections has shown a fluctuating but increasing trend in Finland. The impact of infectious diseases specialist consultation (IDSC) on the antimicrobial therapy of GAS bacteremia has not been studied earlier. A retrospective study on adult GAS bacteremia in The Hospital District of Southwest Finland (HDSWF) was conducted from 2007 to 2018. Data on incidence of bacteremic GAS cases were gathered from the National Infectious Disease Register. Clinical data were obtained by reviewing the electronic patient records. The overall incidence of GAS bacteremia in HDSWF was 3.52/100,000, but year-to-year variation was observed with the highest incidence of 7.93/100,000 in 2018. A total of 212 adult GAS bacteremia cases were included. A record of IDSC was found (+) in 117 (55.2%) cases, not found (-) in 71 (33.5%) cases and data were not available in 24 (11.3%) cases. Among IDSC+ cases, 57.3% were on penicillin G treatment whereas in the group IDSC- only 22.5%, respectively (OR = 4.61, 95% CI 2.37-8.97; p < 0.001). The use of clindamycin as adjunctive antibiotic was more common among IDSC+ (54.7%) than IDSC- (21.7%) (OR = 4.51, 95% CI 2.29-8.87; p < 0.001). There was an increasing trend in incidence of GAS bacteremia during the study period. Narrow-spectrum beta-lactam antibiotics were chosen, and adjunctive clindamycin was more commonly used, if IDSC took place. This highlights the importance of availability of IDSC but calls for improved practice among infectious diseases specialists by avoiding combination therapy with clindamycin in non-severe invasive GAS infections.